Postictal behavior after two types of cortical epileptic afterdischarges in rats - Mikulecká, A; Mares, P (Epilepsy & behavior, 2007)
OBJECTIVE: The aim of this study was to determine if behavioral patterns during the postictal state depend on the type of seizure. METHODS: Rhythmic electrical stimulation of sensorimotor cortex can elicit two types of epileptic afterdischarges (ADs) in adult rats: the spike-and-wave type accompanied by clonic convulsions, and a transition to a nonconvulsive type characterized by behavioral automatisms (mixed type). Rats in which stimulation did not induce ADs constituted the control group. The behavior of the animals was recorded for 20 minutes after the end of ADs or stimulation. RESULTS: Stimulation elicited only shortlasting minimal changes in control rats. Spike-and-wave ADs led to alternation of normal and unsteady walking, a decrease in normal sitting and lying (rigid lying appeared instead), and wet dog shakes (WDS). Mixed-type ADs abolished normal walking and sitting and induced unsteady walking, rigid lying, and a substantial number of WDS. CONCLUSIONS: Abnormal phenomena induced by the two types of ADs differ mostly quantitatively, but also qualitatively.
Keywords: thalamus; péče o zevnějšek u zvířat; Epilepsy; Walking; refrakterní doba elektrofyziologická; krysa rodu Rattus; chůze; mozková kůra; Thalamus; záchvaty; elektrická stimulace; chování zvířat; limbický systém; Electric Stimulation; potkani Wistar; elektroencefalografie; Limbic System; Rats, Wistar; Electroencephalography; Electrodes, Implanted; Grooming; mužské pohlaví; epilepsie; Cerebral Cortex; zvířata; Refractory Period, Electrophysiological; Rats; Animals; Male; Seizures; implantované elektrody; Behavior, Animal